Perceptions of access to harm reduction services during the COVID-19 pandemic among people who inject drugs in metropolitan Chicago. - Kathleen Kristensen; Basmattee Boodram; Wendy Avila; Juliet Pineros; Carl Latkin; Mary-Ellen Mackesy-Amiti (PLoS ONE)
Background The COVID-19 pandemic amplified the risk environment for people who inject drugs (PWID), making continued access to harm reduction services imperative. Research has shown that some harm reduction service providers were able to continue to provide services throughout the pandemic. Most of these studies, however, focused on staff perspectives, not those of PWID. Our study examines changes in perceptions of access to harm reduction services (e.g., participant reported difficulty in accessing syringes and naloxone) among PWID participating in a longitudinal study conducted through the University of Illinois-Chicago's Community Outreach Intervention Projects field sites during the COVID-19 pandemic. Methods A COIVD-19 survey module was administered from March 2020-February 2022 to participants of an ongoing longitudinal study of PWID ages 18-30, who were English-speaking, and were residing in the Chicago Metropolitan Area. Responses to the COVID-19 survey module were analyzed to understand how study participants' self-reported access to harm reduction services changed throughout the pandemic. Baseline responses to the survey were analyzed to compare participant-reported drug use behaviors and perceived access to harm reduction services across COIVD-19 time periods. Mixed effects logistic regression was used to examine difficulty in syringe access as an outcome of COVID-19 time period. Results Participants had significantly lower odds (AOR = 0.28; 95% CI 0.12-0.65) of reporting difficulty in accessing syringes later in the pandemic. However, the majority of participants reported access to syringes and naloxone remained the same as before the pandemic. Conclusions The lack of perceived changes in harm reduction access by PWID and the decrease in those reporting difficulty accessing syringes as the pandemic progressed suggests the efficacy of adaptations to harm reduction service provision (e.g., window and mobile service) during the pandemic. Further research is needed to understand how the COVID-19 pandemic may have impacted PWIDs' engagement with harm reduction services.